The role of pelvic coronal parameters in determining sagittal balance: a prospective radiographic analysis of pelvic spinopelvic alignment in Chinese asymptomatic Han adolescents - Qi, Hao; Zhao, ZengHui; Zu, Feiyu; Wang, Chenchen; Wang, Chenxi; Zhang, Zuzhuo; Wang, Siyuan; Yang, Shuo; Niu, Haiyun; Xue, Rui; Hou, Zhiyong; Chen, Wei; et al. (Frontiers in Pediatrics, 2025)
BackgroundAdolescent idiopathic scoliosis (AIS) is a complex three-dimensional spinal deformity where sagittal alignment significantly influences clinical outcomes. This study aims to analyze spinopelvic balance parameters in asymptomatic adolescents without scoliosis, examining the correlation between pelvic coronal parameters and sagittal balance parameters to validate their use as preliminary indicators in assessing pelvic rotation.MethodsA prospective study was conducted involving 354 adolescents (199 females, 155 males) aged 6–18 years who underwent full-length anteroposterior (AP) and lateral spine radiographs at The Third Hospital of Hebei Medical University between October 2022 and December 2023. Ethical approval and informed consent were obtained. Radiographic assessments included measuring pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), pelvic sacral angle (PSA), and other related parameters. Statistical analysis was performed using SPSS software.ResultsSignificant gender differences were observed in Risser sign distribution and pelvic tilt, with females exhibiting more advanced skeletal maturity. Positive correlations were found between pelvic incidence and pelvic tilt (r = 0.41), and pelvic incidence and sacral slope (r = 0.57), while negative correlations were noted between pelvic incidence and pelvic sacral angle (r = −0.43). Strong correlations between sagittal parameters and newly introduced coronal parameters, such as sacral-femoral-pubic angle and Pubo-Hilgenreiner Distance, were also identified.ConclusionThe study demonstrates that parameters like Iliac tilt, Pelvic sacral angle, Sacral-femoral-pubic angle, and Pubo-Hilgenreiner Distance correlate well with traditional spinopelvic parameters and can be used to assess pelvic sagittal balance in clinical settings. Future research should focus on longitudinal studies to further validate these findings.